1993
DOI: 10.1038/bjc.1993.301
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β expression in the human colon: differential immunostaining along crypt epithelium

Abstract: Summary Samples of colorectal carcinoma, adenoma and normal colorectal mucosa were examined for the expression of TGF-P by immunohistochemistry. Immunoreactivity for TGF-P was present in 52 out of a total of 58 samples of normal mucosa examined. In adenomas and carcinomas TGF-P expression was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 6 publications
5
54
0
1
Order By: Relevance
“…As these processes are critical in the maintenance of tissue homeostasis in the colonic crypt, it is somewhat surprising that relatively little is known about the specific role of the Rb protein in the colon. The differential expression of other proteins within the colonic crypt, for example Bcl-2 Bax, (Krajewski et al, 1994), TGFβ, (Avery et al, 1993), and IGFBP-3 (Williams et al, 2000), have given important clues as to their function in the regulation of crypt architecture. Therefore we investigated the expression of pRb in the normal colonic crypt in vivo, and the mechanism of regulation of pRb expression with differentiation and apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these processes are critical in the maintenance of tissue homeostasis in the colonic crypt, it is somewhat surprising that relatively little is known about the specific role of the Rb protein in the colon. The differential expression of other proteins within the colonic crypt, for example Bcl-2 Bax, (Krajewski et al, 1994), TGFβ, (Avery et al, 1993), and IGFBP-3 (Williams et al, 2000), have given important clues as to their function in the regulation of crypt architecture. Therefore we investigated the expression of pRb in the normal colonic crypt in vivo, and the mechanism of regulation of pRb expression with differentiation and apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…As differential expression of proteins along the axis of the normal colonic crypt has previously given important clues as to their function in the colonic crypt (for example Avery et al, 1993;Williams et al, 2000), the expression of pRb and related pocket proteins (p107 and p130) was investigated for at least 10 sections from different patients of normal colonic mucosa and tissue adjacent to colon tumours where appropriate. Blocking peptides for each antibody were used as a control to ensure that antibody staining was specific (refer to materials and methods, data not shown).…”
Section: Rb Protein and Related Proteins P107 And P130 Are Differentimentioning
confidence: 99%
“…sodum butyrate, to proceed through a differentiation programme. Indeed, the presence of TGFb 1 protein expression in the non-proliferating region of the human colonic cryptic (Avery et al, 1993), may suggest a role for the growth factor in mediating a stable growth arrest which is a prerequisite for differentiation. In addition, differentiating agents such as HMBA, retinoid acid and sodium butyrate can induce TGFb 1 expression (Glick et al, 1989;Schroy et al, 1990;Barnard and Warwick, 1993) suggesting some interaction between these factors in the maintenance of a differentiated phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This autocrine growth inhibitor has been demonstrated to negatively regulate intestinal epithelial cell growth in vitro (Barnard et al, 1989;Hoosein et al, 1989;Manning et al, 1991;Geiser et al, 1992;Wu et al, 1992). In addition, immunostaining for TGFb 1 protein expression in the normal human colonic mucosa has shown it to be differentially expressed within epithelial cells of the crypt, with enhanced immunoreactivity in the non-proliferating more differentiated cells in the upper parts of the crypt and an absence of expression in the lower proliferating cell compartment (Avery et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for such a molecule has been far from conclusive . Studies investigating extrinsic controls have included factors such as TGF␣ (Avery et al, 1993) and cell adhesion molecules (Beaulieu, 1992). Investigators have reported spatially regulated expression of such factors along the crypt-villus axis or along the crypt column.…”
Section: Discussionmentioning
confidence: 99%